Documenting data-ghosts: Visualising non-human life and death through what is undocumented in early childhood education - Albin-Clark, Jo (Journal of Posthumanism, 2023)
What happens with ethical response-abilities that linger in early childhood education documentation practices? Thinking-with research-creation, I problematise the human focus of three and four-year old children caring for eggs in a classroom hatchery. Foregrounding non-human life (and death) brings an ethical disquiet that sticks around. Instead, the past-present-future becomes blurred with ghostly matters. What is particularly haunting is the disposability of non-human life after human educational events are over. Haunting data that is not easy to think with and irritates through time is conceptualised as a data-ghost. Through methodological creative experiments inspired by digital visualisations of non-human data-ghosts, I ponder with the minor of what is unthought, half-said and non-documented when chicks are returned to commercial hatcheries. Posthuman praxis leads me to trouble the human-centric focus of documentation practices and wonder what new questions are generated for multi-species flourishing when the foreground slips and flips to the non-human.